Improving psychosocial services for vulnerable families with young children: strengthening links between health and social services in Germany. (7th December 2018) - Renner, Ilona; Saint, Victoria; Neumann, Anna; Ukhova, Daria; Horstmann, Sabine; Boettinger, Ullrich; Dreibus, Martina; Kerl-Wienecke, Astrid; Wulff, Pilar; Mechthild, Paul; Thaiss, Heidrun
Abstract : Ilona Renner and colleagues describe cross-sectoral collaborative efforts in Germany to enhance the skills of parents to care for young children